2008
DOI: 10.1007/s10522-008-9163-5
|View full text |Cite
|
Sign up to set email alerts
|

Chinese herbal medicine for Mild Cognitive Impairment and Age Associated Memory Impairment: a review of randomised controlled trials

Abstract: This review assesses the effectiveness and safety of Chinese herbal medicines (CHM) for Mild Cognitive Impairment (MCI) and Age Associated Memory Impairment (AAMI). Electronic searches of English and Chinese databases and hand searches of Chinese journal holdings were conducted. Randomised controlled trials comparing orally administered CHM with placebo, no intervention or other therapy were considered. Ginkgo biloba was excluded. Ten trials met inclusion criteria. Eight different CHM were investigated. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…Previous reviews of clinical studies have reported potential effectiveness of some Chinese herbs and herbal formulae for MCI but these were conducted five or more years ago, so an update is warranted (May et al ., ; Han et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous reviews of clinical studies have reported potential effectiveness of some Chinese herbs and herbal formulae for MCI but these were conducted five or more years ago, so an update is warranted (May et al ., ; Han et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Such difference might be attributed to the high accessibility and full coverage of TCM in Taiwan's national health insurance scheme (Chen et al, 2007). Moreover, several clinical studies showed that TCM formulae could be safe and beneficial to dementia patients (Man et al, 2008;May et al, 2009), and such knowledge might encourage TCM use (Hillmer et al, 2006). The incidence rate of dementia in Taiwan over the 12 years of study was 1.8%, which is relatively low compared with former cohort studies in Chinese population (Wu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…From our previous analysis of well-designed, randomized double-blind controlled trials on Chinese herbal medicines beneficial for the improvement of cognitive function, we found that neuroprotective benefits of suppression of oxidative stress as the most common feature provided by single herbs or herbal mixtures (May et al 2009.…”
Section: Herbal Polyphenols -Modulation Of Oxidative Stress Dementiamentioning
confidence: 99%